CORPORATE ACADEMIC DISHONESTY AS A PROBLEM OF THE UNIVERSITY SOCIAL RESPONSIBILITY - Volodymyr Riabchenko (Неперервна професійна освіта: теорія та практика, 2021)
The article deals with the problem of corporate academic dishonesty, without overcoming which it is impossible to ensure the quality of national higher education to meet modern world requirements. The article aims to actualize the problem of corporate academic dishonesty in the educational process of domestic universities and other higher education institutions, as well as to identify and explain the key reasons that give rise to the phenomenon and does not allow HEIs to be socially responsible. The essence of the social responsibility of the university is identified. It is emphasized that it cannot be provided when corporate academic dishonesty is cultivated in the university environment. The key causes of the problem of academic dishonesty in domestic universities and other higher education institutions are highlighted. A methodological approach to assessing the possibilities of ensuring real integrity in the social environment of a higher education institution depending on the model of its educational activities is proposed. According to the results of the study, it is concluded that corporate academic dishonesty is a systemic social disease of domestic higher education, which is caused by the state of modern Ukrainian society. It is a much more dangerous problem compared to plagiarism in improving the quality of Ukrainian higher education to the level of European requirements. And it is much more difficult to overcome than the fight against plagiarism. This is because plagiarism is committed individually and corporate academic dishonesty is done collectively. This determines the need for in-depth systemic studies of the actualized problem and the determination of ways to overcome it.